(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Chronic kidney disease (CKD) patients on Maintenance Hemodialysis (MHD) frequently present to emergency departments with acute, life-threatening conditions, primarily cardiovascular emergencies, sepsis, and metabolic abnormalities. CKD is a significant global health burden with rising prevalence, particularly in India, where diabetic nephropathy is a leading cause of End-Stage Renal Disease (ESRD). Understanding acute presentations and their management is crucial to improving long-term outcomes and reducing morbidity and mortality in this vulnerable population. Methods: This prospective observational study, conducted in the General Medicine Department of KIMS Hospital from November 2018 to September 2020, evaluated 50 CKD patients on maintenance hemodialysis (MHD) meeting NKF KDOQI criteria. Patients were assessed through history, clinical examination, and investigations, with interventions provided for life-threatening complications like hyperkalemia, metabolic acidosis, and pulmonary edema. Outcomes (improved, died, status quo) were documented, and data were analyzed using SPSS with statistical tests like Chi-Square and Mann-Whitney U, with significance set at *P* < 0.05. Conclusion: The study highlighted sepsis as the leading cause of mortality in CKD patients, with cardiovascular diseases and acute pulmonary edema being major contributors to hospital admissions. Early risk identification, cardiovascular interventions, and maintaining optimal serum potassium, hemoglobin, and anemia levels can improve outcomes. Prompt recognition and treatment of uremic encephalopathy and reducing frequent ED visits are crucial for lowering morbidity and mortality. Effective assessment and management by ED physicians play a vital role in enhancing patient care and survival.